2021
DOI: 10.1021/acsbiomaterials.1c00982
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Nanofibers by Physical Adsorption of Fiber-Homologous Amphiphilic Copolymers and Nanofiber-Reinforced Hydrogels with Excellent Tissue Adhesion

Abstract: Herein, we report a simple approach to modify hydrophobic PCL nanofibers by adsorption of a fiber-homologous amphiphilic triblock copolymer (PCL-b-PEG-b-PCL, PCEC). The modified PCL nanofibers were then utilized to reinforce a physical hydrogel, which was formed by micellar crosslinking of the same PCEC triblock copolymer. Therefore, the copolymer played a dual role in not only dispersing and stabilizing nanofibers but also additionally providing a framework for the hydrogel matrix. The mechanical strength of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“… 43 Finally, the hydrogen bonds that the free PEO segment in F127DA can form with protein-rich substrates, and the hydrophobic interactions provided by the PPO segment with the cell membrane, promote the adhesion properties of the hydrogel. 44 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 43 Finally, the hydrogen bonds that the free PEO segment in F127DA can form with protein-rich substrates, and the hydrophobic interactions provided by the PPO segment with the cell membrane, promote the adhesion properties of the hydrogel. 44 …”
Section: Resultsmentioning
confidence: 99%
“…43 Finally, the hydrogen bonds that the free PEO segment in F127DA can form with protein-rich substrates, and the hydrophobic interactions provided by the PPO segment with the cell membrane, promote the adhesion properties of the hydrogel. 44 In vitro burst pressure test Hydrogels that bind tightly to tissues can complement or even replace sutures and staples. The burst pressure is a key metric for assessing the sealing properties of hydrogels for bladder repair.…”
Section: Biocompatibility Of the Hydrogels And Wound Healing Assaymentioning
confidence: 99%
“…The release capacity of the therapeutic drugs decreased and the functionality of the surface immobilized biomolecules is well maintained. This technique is used also in gene delivery, due to its prolonged and slow release behavior 114 . Surface modification can also be done in blended electrospun nanofibers, which may increase the slow release behavior of biomolecules 114 .…”
Section: Selectivity Of Polymermentioning
confidence: 99%
“…So there is a need for the surface modification of synthetic nanofibers with natural biopolymers using post‐treatment method to improve their bioavailability. Modified surface of nanofiber mats with bioactive molecules will enhance the specific phenotype cell growth as in tissue engineering, which involves biologically active molecules and directly interact with the surface of cells 114 . So, this technique is mainly used in tissue engineering.…”
Section: Selectivity Of Polymermentioning
confidence: 99%
“…Zhong et al reported the preparation of nanofiber reinforced hydrogels with excellent tissue adhesion. 79 The polycaprolactone-poly(ethylene glycol) (PCEC) micelles were shown to absorb onto the surface of PCL films or fibers, increasing their hydrophilicity and thereby assisting in the homogeneous dispersion of nanofibers in the hydrogel. The nanofiber/hydrogel combination has greater adhesion burst pressure on pigskin and muscle than commercial fibrin glue, indicating considerable potential for tissue sealing and hemorrhage control.…”
Section: Poly(ε-caprolactone) (Pcl)mentioning
confidence: 99%